2009
DOI: 10.1038/ki.2008.581
|View full text |Cite
|
Sign up to set email alerts
|

A method for monitoring vascular access function during hemodialysis

Abstract: We tested a new bedside method to determine the function of native arteriovenous fistula in 16 patients performed during hemodialysis without stopping the treatment. We initially measured vascular access flow (Q(a)) in each patient using the Transonic HD01(plus) device. We then measured the pressure in arterial and venous drip chambers at different blood pump flow rates (Q(bset)=0, 50, 100, 250, 300, 350 ml/min). The intravascular blood pressure gradient (P(f)) between arterial and venous puncture sites was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Physical examination combined with urea dilution may be an alternative for detecting AVF stenosis when Doppler ultrasound is not available. Several studies demonstrated a role of both urea and ultrasound dilution in the detection of recirculation and abnormal access ow [14,21,28,33,35,36] Our study had some limitations. Firstly, it is single-center nature with small patient numbers.…”
Section: Discussionmentioning
confidence: 88%
“…Physical examination combined with urea dilution may be an alternative for detecting AVF stenosis when Doppler ultrasound is not available. Several studies demonstrated a role of both urea and ultrasound dilution in the detection of recirculation and abnormal access ow [14,21,28,33,35,36] Our study had some limitations. Firstly, it is single-center nature with small patient numbers.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies demonstrated a role of both urea and ultrasound dilution in the detection of recirculation and abnormal access flow (13,20,27,30,32,33) Our study had some limitations. Firstly, it is single-center nature with small patient numbers.…”
Section: Discussionmentioning
confidence: 88%
“…Physical examination combined with urea dilution may be an alternative for detecting AVF stenosis when Doppler ultrasound is not available. Several studies demonstrated a role of both urea and ultrasound dilution in the detection of recirculation and abnormal access ow [14,21,28,33,35,36] Our study had some limitations. Firstly, it is single-center nature with small patient numbers.…”
Section: Discussionmentioning
confidence: 91%